Erratum: Search for photons with energies above 1018 eV using the hybrid detector of the Pierre Auger Observatory - Aab, A.; Abreu, P.; Aglietta, M.; Al Samarai, I.; Albuquerque, I. F. M.; Allekotte, Ingomar; Almela, A.; Alvarez Castillo, J.; Alvarez-Muñiz, J.; Anastasi, G. A.; Anchordoqui, Luis A.; Andrada, B.; et al. (IOP Publishing, 2020)
Fil: Aab, A.. Radboud Universiteit Nijmegen; Países Bajos